MASALAH KETENAGAKERJAAN DAN PENGANGGURAN DI INDONESIA - Ahmad Soleh (Fakultas Ekonomi Universitas Pasir Pengaraian, 2017)
This paper deals with the problems of employment and unemployment, there should be discussion of the issues as a barrier to creating jobs, employment, and unemployment in order to increase and accelerate the economic growth of this country. In an effort to create the labor market is the key to ease of doing business. Implementation of policies that are not giving out the policy of convenience for the private and the world need to initiate and carry out business activities in Indonesia, including the lengthy licensing procedures, costs Mahan and long processing time. Is a major limiting factor in creating quality jobs. Institutional aspects is a key element that needs to be fixed in an effort to bring down unemployment. Pentingknya institutional aspects in solving development problems (institutionmatter), including creating and expanding employment opportunities. Institutional aspects laws regulate the public good in the rules of formal and non-formal rules.